The effects of project-based learning on environmental literacy - Karayol, Sevgi Aslıhan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
The aim of the present study was to explore the effects of project-based learning on 9th grade students’ environmental literacy and science process skills. Environmental literacy is the key to protect environment and find solutions to environmental problems. The sample of this study was 78 students from a vocational and technical high school for girls. One of the classes was randomly assigned as experimental group (called Group PB, N=40) and taught the topic 'environmental problems’ through project-based learning method. They worked in groups to develop their own projects using scientific method and science process skills for an environmental problem they chose. The other group (called Group TC, N=38) learned about the same topic with teacher-centered instructional method. The two teaching methods were implemented by the researcher. The data collection tools utilized for the study were Environmental Literacy Test (ELT) that consisted of three parts, namely, knowledge, attitude, behaviour, and Science Process Skills Test (SPST). Both tests were given before and after the treatments and semi-structured interviews were conducted with eight students from each class. According to the analysis of ELT-Pre, ELT-Post, SPST-Pre and SPST-Post, it was found that Group TC improved their scores in environmental knowledge and attitude components of environmental literacy, but Group PB improved their scores in all the components (environmental knowledge, environmental attitude, and environmental behavior) of environmental literacy and science process skills. According to the comparison of the Post-tests, Group PB students performed better than Group TC students in all tests. In the interviews, Group PB students mentioned many themes and codes that belong to environmental literacy components and science process skills, which indicated that they developed a more enriched point of view than Group TC students. Furthermore, Group PB students gained lots of social skills such as selfconfidence, group work, loving lessons, etc. as a result of project-based learning.
Keywords: Project method in teaching.; Environmental literacy -- Study and teaching (Secondary)